The music of indifference - Cueto, Sergio (Universidad Nacional del Litoral, 2018)
Analyzing a Beckett’s poem, we will try to characterize not only his music conception but also the music we listen in his work. To accomplish this, it will be required to articulate the question of the voice with the motives of silence and murmuring, pain and desert. Therefore, it will be possible to characterize the «music of the indifference» as a music without progress or resolution, without identity or interiority, only equal to his own unlikeness —indifferent, as the poem says.